2022
DOI: 10.1111/liv.15278
|View full text |Cite
|
Sign up to set email alerts
|

The DEAD‐box helicase DDX3x ameliorates non‐alcoholic fatty liver disease via mTORC1 signalling pathway

Abstract: Background & Aims: The DEAD (Asp-Glu-Ala-Asp)-box helicase family member DDX3x has been proven to involve in hepatic lipid disruption during HCV infection.However, the role of DDX3x in non-alcoholic fatty liver disease (NAFLD), in which lipid homeostasis is severely disrupted, remains unclear. Here, we aimed to illustrate the potential role of DDX3x in NAFLD. Methods: DDX3x protein levels were evaluated in NAFLD patients and NAFLD models via immunohistochemistry or western blotting. In vivo ubiquitin assay was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
(81 reference statements)
0
5
0
Order By: Relevance
“…A previous study demonstrated that the protein level of DDX3X was decreased in NAFLD patients [ 7 ]. We further analyzed the Gene Expression Omnibus (GEO) database with a larger sample size of 151 NAFLD/NASH patients and 28 controls (GSE213621) and reached the same conclusion that DDX3X expression was decreased in NASH patients (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study demonstrated that the protein level of DDX3X was decreased in NAFLD patients [ 7 ]. We further analyzed the Gene Expression Omnibus (GEO) database with a larger sample size of 151 NAFLD/NASH patients and 28 controls (GSE213621) and reached the same conclusion that DDX3X expression was decreased in NASH patients (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Persistent hepatic cellular metabolic stress and liver inflammatory stimuli are key signatures of NASH, suggesting that DDX3X may play a crucial role in NASH progression. Previous investigation has shown that DDX3X reduces steatosis during NAFLD progression [ 7 ]. However, the role of DDX3X in inflammation is not fully explored, and the function of DDX3X in NASH remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Altered expression of CEACAM1 [176], ACSL1 [285], STAT1 [286], TLR4 [287], ABCA1 [288], TLR5 [183], F2RL1 [289], CYP2D6 [290], PDK4 [291], RNF213 [186], JAK2 [292], TLR8 [189], NOTCH2 [293], CENPJ (centromere protein J) [294], FNIP1 [295], TLR2 [296], KIDINS220 [297], DUSP6 [298], CYP1B1 [299], S1PR3 [300], NCOA2 [301], HDAC9 [302], PELI1 [303], EGR1 [304], HIF1A [305], CCR2 [306], IRAK3 [307], KLF3 [308], VEGFA (vascular endothelial growth factor A) [309], OGT (O-linked N-acetylglucosamine (GlcNAc) transferase) [310], PHLPP1 [213], FMR1 [311], IGF2R [312], PRKAR1A [313], WDR11 [314], LDLR (low density lipoprotein receptor) [315], TLR6 [316], SIRT1 [317], ALDH1A1 [318], NOD2 [319], ACSL4 [320], ELOVL6 [321], VCAN (versican) [322], CLIC5 [323], CLCN3 [324], OSBPL11 [162], HELZ2 [325], TET2 [326], KDM6A [327], PHF2 [328], PHGDH (phosphoglycerate dehydrogenase) [329], VEGFB (vascular endothelial growth factor B) [330], ZBTB7A [331], PC (pyruvate carboxylase) [332], CCR7 [333], PRDX2 [334], MAF1 [335], HSPB1 [336], ESF1 [281], LGALS3 [337], OLFM2 [338] and HDAC11 [339] had been confirmed in obesity. CEACAM1 [340], ACSL1 [341], TLR4 [342], ABCA1 [343], TLR5 [344], CYP2D6 [345], JAK2 [346], NOTCH2 [347], DDX3X [348], NCOA4 [349], EGR1 [350], IQGAP2 [351], GCLC (glut...…”
Section: Discussionmentioning
confidence: 99%
“…Based on the miRNA-hub gene regulatory network and TF-hub gene regulatory network constructed by the online database miRNet and NetworkAnalyst, we identified hub genes, miRNAs and TFs. Previous study showed that DDX3X [348], EGR1 [350] and SREBF1 [539] were associated with non-alcoholic fatty liver disease. EGR1 [84], HIF1A [88], STAT1 [60], hsa-mir-16-5p [540], hsa-mir-532-3p [541], hsa-mir-503-5p [542], SREBF1 [543] and FOXP3 [544] plays a pivotal role in the atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%